Los medios de comunicación como actores políticos - Chávez Infante, Tania Vanesa (2013)
The study of political communication and is closely related to public space, is this is to create the new logic of participation, representation and citizenship policy stakeholders. And it is the evolution of communication processes has been what has set another political map interaction and other behaviors of urban formation, and therefore other factors of political power in Ecuador. So taking the case of the power struggle between the state and the media of our country (print), since it is in this political context where there are clearly changes in behavior and political communication born in Ecuador. Therefore take the new political discourse and communication that is structured within the various media and the discourse of the state; important aspects imaginary change in a society in which the media have become more transmitters influential campaign processes, established governments, whether their messages in favor or against them. And as already mentioned it this technological development has made communications to establish a media culture, both in social relations and in the policies. The communication and information systems have privileged means; this actually makes communication problems respond primarily to specific interests of sectors of economic and political power.